Examining Adoption and Effectiveness of WhatsApp as a Marketing Tool: An Example of an Austrian Fitness and Health Center - Brauer, Claudia; Pronnet, Julia; Zehrer, Anita (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This study explores the factors influencing user acceptance and intention to use WhatsApp as a business-to-consumer (B2C) communication and marketing tool in the fitness industry, using an Austrian fitness center as a case study. Given WhatsApp's growing commercial relevance, understanding customer interaction determinants is crucial. Despite the overall growth of the fitness sector, businesses face challenges that necessitate innovative communication strategies. Grounded in the Technology Acceptance Model, the Theory of Planned Behavior, and the Theory of Reasoned Action, this research identifies twelve key acceptance factors. A quantitative deductive approach was applied, and survey data were analyzed using multiple linear regression. The findings reveal that perceived value, attitude towards use, and perceived ease of use significantly influence the intention to use WhatsApp. Additionally, perceived usefulness correlates positively with perceived ease of use and the perceived informational and entertainment value. These insights highlight WhatsApp's potential as a marketing and communication tool in the fitness industry. The study offers a foundation for further research and provides practical implications for optimizing business performance through targeted marketing and customer engagement strategies.